Legal Study on The Criminal Offense of Tax Invoice Forgery That Has Received Tax Amnesty - Siregar, Rischad Widianto; Sinaga, Niru Anita; Gaol, Selamat Lumban (Magister Ilmu Hukum Fakultas Hukum Universitas 17 Agustus 1945 Surabaya, 2024)
This study aims to determine how the legal consequences of criminal acts of falsification of tax invoices that have received tax amnesty. Criminal acts in the field of taxation are violations of the rules of the tax law that cause state financial losses and people who commit criminal acts can be prosecuted criminally. /Falsification of tax invoices is a concern of legal problems among the community that has the potential to harm state revenue. Many people falsify tax invoices but do not understand the impact on the state. By falsifying tax invoices, the taxpayer will reduce their tax payable. This research uses normative legal research methods with a statutory approach, conceptual approach, secondary data type. As a result of this study, researchers found a form of criminal liability for the criminal act of falsifying tax invoices that have obtained tax amnesty in criminal law in Indonesia, in the form of excuse (schulduitsluitingsgrond-faits d'exuce) as a reason for criminal elimination (strafuitsluitingsgronden), so that the perpetrator should be stopped from investigating at the investigation level or if it has entered the trial stage, the Panel of Judges should issue a verdict of release from all legal charges for the actions committed by the defendant (ontslag van recht vervolging), even though the Criminal Act of Falsification of Tax Invoice is proven or the unlawful nature is not lost, but the defendant cannot be held criminally responsible, because there are reasons that excuse according to the law.